Body mass index awareness using game-based learning in Malaysia: game design and initial user experiences - Nasharuddin, Nurul Amelina; Marlisah, Erzam; Mohd Nazan, Ahmad Iqmer Nashriq; Ab. Jalil, Habibah; Ismail, Ismi Arif; Ma'rof, Aini Marina; Salim, Siti Suria (IEEE, 2019)
Mobile-based gaming applications can motivate and facilitate in educating adolescents in health awareness and further can prevent obesity. The purpose of this paper was to observe and assess the initial acceptance of a prototype mobile game application in promoting a healthy Body Mass Index among adolescents. Based on the observations, the developed game was found to be interesting and has positive feedback. Positive user experiences were being expressed on the game's style and aesthetics, operability, learnability, autonomous learning, enjoyment, and social interaction offered. All of these added the excitements of the players and most of them were looking forward to continuing playing in the future. However, some challenges were reported, related to the player's confidence, challenges offered and winning opportunity. The positive findings and concerns discovered during the testing session are reported in this paper. Good health promotion via game-based learning using mobiles demonstrates the potential to offer enjoyment and feasible for adolescents although in our case, further usability testing with larger-scale of participants and a longer session is needed